2013
DOI: 10.3109/13625187.2013.819077
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing women's selection of combined hormonal contraceptive methods after counselling in 11 countries: Results from a subanalysis of the CHOICE study

Abstract: Women's choice of CHC methods after contraceptive counselling are influenced by their age, educational background, relationship status, prior unplanned pregnancies and country of residence, as well as age, gender and preferences of their HCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
0
15
0
3
Order By: Relevance
“…16,17 In addition, there is a small body of evidence supporting the value of both relational and task-oriented communication. Several observational studies in the United States have found a relationship between the interpersonal quality of family planning counseling and contraceptive use.…”
Section: What Is the Evidence That Contraceptive Counseling Matters?mentioning
confidence: 99%
“…16,17 In addition, there is a small body of evidence supporting the value of both relational and task-oriented communication. Several observational studies in the United States have found a relationship between the interpersonal quality of family planning counseling and contraceptive use.…”
Section: What Is the Evidence That Contraceptive Counseling Matters?mentioning
confidence: 99%
“…Thirty-seven percent reported that neither of their parents had more than a high school education. Thirty-eight providers participated in the study; on average, they contributed nine visits each (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Visits were well distributed by provider age: Some 37% were with providers younger than 46, while 36% were with providers aged 46-55 and 27% were with providers aged 56 or older.…”
Section: Overall Mention Of Iudsmentioning
confidence: 99%
“…5 In the United States, however, IUD use, while increasing, has remained relatively low; the most recent results from the National Survey of Family Growth indicate that 8% of women are currently using this method. 6 Women' s selection of a new contraceptive method is infl uenced by provider counseling, 7,8 so family planning providers may be contributing to the underuse of IUDs in the United States. Misinformation among providers may be one factor.…”
mentioning
confidence: 99%
“…Studies investigating the effect of counseling have found that over 50% of women who undergo it report that their provider influenced their choice of method,(2) and this influence may be particularly marked with respect to choice of newer methods. (2, 3) Other studies have found that women who experience higher quality interpersonal care have better contraceptive outcomes. (47) Quality contraceptive counseling can therefore have a powerful influence on women’s abilities to achieve their reproductive goals.…”
Section: Introductionmentioning
confidence: 99%